Struggling with memory: anguish and hope in selected pandemic poems by migrant workers in Singapore - Moratilla, Noel Christian A. (Frontiers in Sociology, 2024)
The pandemic has tested the fortitude and resilience of a huge swath of humanity. Even measures undertaken to address the pandemic, primarily the massive vaccination campaigns, revealed a glaring disparity between and within societies. The collective grief, anxiety, and desire for survival have led to creative ways to contend with the crisis. Poetry has served as one of those strategies. This paper revolves around selected pieces of poetry particularly those with themes related to being an Asian migrant worker during the pandemic. The primary themes drawn from the poems are as follows: dealing with the changes brought about by the pandemic; concern over family; job precarity and stigmatization; and hope and resilience.